A simple fluorescence-based lateral flow test platform for rapid influenza B virus screening. Issue 14 (22nd March 2021) - Wiriyachaiporn, Natpapas; Sirikaew, Siriwan; Bamrungsap, Suwussa; Limcharoen, Thanchanok; Polkankosit, Pannarai; Roeksrungruang, Pimporn; Ponlamuangdee, Kanyawan
Abstract : A simple and rapid fluorescence-based screening platform for influenza B virus using a one-step Cy5-SiNPs–mAb bioconjugation on lateral flow-based technique. Abstract : A simple fluorescence-based lateral flow test platform for rapid influenza B virus screening as a model target molecule was successfully developed. In this work, Cy5-loaded silica nanoparticles were directly conjugated to monoclonal antibodies, specific to the influenza B nucleoprotein, via a direct physisorption method and used as detector probes. Using this approach, the signal response to the detection was further determined using a fluorescent signal intensity measurement method via a portable reader, in combination with fluorescence imaging analysis. The degree to which the fluorescence signal response is detected is proportional to the amount of the target virus protein present in the system, reflected by the accumulation of the formed particle–antibody conjugates within the test system. Under optimized conditions, the system is capable of detecting the influenza B virus protein at a level of 0.55 μg per test within 30 min, using small sample volumes as low as 100 μL ( R 2 = 0.9544). In addition to its simplicity, further application of the system in detecting the influenza B virus protein was demonstrated using the viral transport media as specimen matrices. It was also shown that the system can perform the detection without cross-reactivity to other closely related respiratory viruses.